“The concentration of power, represented by current prevailing media conditions, is and ought to be open to challenge.” An interview with Peter Golding - Jernej Amon Prodnik; Sašo Slaček Brlek; Peter Golding (tripleC: Communication, Capitalism & Critique)
Interview with Peter Golding, Emeritus Professor at Northumbria University, Visiting Professor in the School of Arts and Cultures at Newcastle University and one of the crucial figures in Critical Political Economy of Communication. In the interview we discuss the role of critical scholarship, the sometimes troubled relationship between cultural studies and critical political economy of communication, the importance of a sociological perspective in studying media, and the impact of broader socio-political trends on academia.